2015
DOI: 10.4103/0972-2327.165453
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance angiographic evaluation of circle of Willis: A morphologic study in a tertiary hospital set up

Abstract: Background:Anatomy of circle of Willis (CW) shows wide variation in different individuals, population groups, and has vital clinical significance in causation and presentation of clinical disease. This study evaluates the anatomical variations, incidence of various common anomalies of CW in south Indian tertiary hospital set up, using three-dimensional time-of-flight (3D-TOF) magnetic resonance angiography (MRA).Materials and Methods:A total of 300 patients referred for neuroimaging study over a period of 2-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
3
3
0
1
Order By: Relevance
“…This configuration was seen in 69.8% (n=37) and 90.2% (n=37) of males and females, respectively. This finding is similar to studies done by Naveen SR et al and Dr. Arjun Bhaddur et al which showed type A variant being the most common anterior circulation variant [27, 28].…”
Section: Discussionsupporting
confidence: 92%
“…This configuration was seen in 69.8% (n=37) and 90.2% (n=37) of males and females, respectively. This finding is similar to studies done by Naveen SR et al and Dr. Arjun Bhaddur et al which showed type A variant being the most common anterior circulation variant [27, 28].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar with findings of Jalali Kondori et al [9] 5.7% and 0.95%, Chen et al [1] 5.92% with 1.38%. Duplication of ACoA occurred in 0.6%, or 3 patients, 0.3% in female and 0.9% in men, comparing with similar results of 0.95% [9] or 0.6% [14]. When an intracranial aneurysm ruptures, it causes subarachnoid haemorrhage.…”
Section: B C Asupporting
confidence: 52%
“…15,16 Moreover, in 8% to 13% of patients both ACAs are supplied by only one internal carotid artery (ICA) due to an absent or hypoplastic A1 segment of the circle of Willis (CoW). [17][18][19] When monitoring is restricted to assessing frontal lobe perfusion, even widespread cerebral perfusion changes due to problems with the other carotid artery can remain undetected. 16 In a previous study, we have already shown that using multichannel continuous-wave near-infrared spectroscopy (CW-NIRS) to evaluate the effectiveness of collateral circulation might serve as an objective and early predictive marker of critical perfusion during percutaneous transluminal angioplasty or balloon occlusion testing of an ICA.…”
Section: Introductionmentioning
confidence: 99%